Plerixafor as a salvage mobilization strategy for haploidentical peripheral blood allogeneic stem cell transplantation. Issue 9 (15th July 2015) - Nadeau, Michelle; George, Laeth; Yeager, Andrew M.; Anwer, Faiz; McBride, Ali
Key Clinical Message: In allogeneic stem cell mobilization, peripheral blood stem cell mobilization with filgrastim can be considered standard of care. Poor mobilizers may be at risk for inadequate stem cell collection during apheresis. He we present a successful case of salvage plerixafor use with filgrastim in a haploidentical identical transplant patient. Abstract : In allogeneic stem cell mobilization, peripheral blood stem cell mobilization with filgrastim can be considered standard of care. Poor mobilizers may be at risk for inadequate stem cell collection during apheresis. Here, we present a successful case of salvage plerixafor use with filgrastim in a haploidentical identical transplant patient.